UV-VIS SPECTROELECTROCHEMICAL IN SITU STUDY DURING THE ELECTROSYNTHESIS OF COPOLYMERS - Del Valle, M. A.; Motheo, A.; Ramírez, A. M. R. (Journal of the Chilean Chemical Society, 2019)
In this work, the synthesis of poly(aniline-co-o-methoxyaniline) is performed using purely electrochemical techniques, coupled to UV-vis spectroscopy in situ, in 3D. The electrocopolymerization is carried out on ITO electrodes, in various monomer ratios aniline/o-methoxyaniline varying between 0.1 to 0.4 mol L-1 in H2SO4 1.0 mol L-1. The homo- and copolymers were characterized by cyclic voltammetry, in situ UV-Visible, and scanning electron microscopy. The results show the important information provided by UV-Visible spectroscopy coupled with electrochemical techniques. Thus, it is observed that the reactivity that gives the o-methoxy group in the aniline ring, damages the conductivity of the polymer, due to the occlusion of oligomers of N-phenyl-1,4-benzoquinonediimine and/or with the structure of oxazine. On the other hand, the SEM images show morphological changes associated with the progress of the synthesis, which can be related with the less conductivity produced by o-methoxy, despite the greater reactivity.